Utilization of Social Media (Instagram, Twitter and Facebook) as Educational Means Regarding Beauty Standards in the You're Enough Program - Yuda Pratama, Muhammad; Rifky Fadhillah, Febian; Mandela, Dohan (PT Literasi Nusantara Publisher, 2023)
The beauty standard created is a reinforcement of the media, one of which is social media. Social media influences shaping beauty standards which then generalizes the perception of the Indonesian people about the concept of